2015
DOI: 10.1016/j.bjid.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines for surgical antibiotic prophylaxis: a review

Abstract: Significant variations were observed in all the outcomes assessed, and all the studies indicated a need for greater adherence to guidelines for surgical antibiotic prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 23 publications
4
45
1
12
Order By: Relevance
“…In their systematic review of adherence to surgical antibiotic prophylaxis protocols, Gouvêa et al 35 concluded that all the studies reviewed indicated the need for greater adherence to such protocols. In our study, despite the outcomes "correct antibiotics choice" and "discontinuation of antibiotic at the right time" having reached rates close to 100%, the other two outcomes did not show sufficient results.…”
mentioning
confidence: 99%
“…In their systematic review of adherence to surgical antibiotic prophylaxis protocols, Gouvêa et al 35 concluded that all the studies reviewed indicated the need for greater adherence to such protocols. In our study, despite the outcomes "correct antibiotics choice" and "discontinuation of antibiotic at the right time" having reached rates close to 100%, the other two outcomes did not show sufficient results.…”
mentioning
confidence: 99%
“…This has made the introduction of and adherence to such strategies the focus of research from a range of medical fields over recent decades (Prior, Guerin, & Grimmer-Somers, 2008;Tomasone, Chaudhary, & Brouwers, 2015). Several studies suggest that nonadherence to guidelines is widespread among health professionals (Corallo et al, 2014;Gouvêa, Novaes, Pereira, & Iglesias, 2015). Nonetheless, health professionals believe that the variability in clinical practice is not worrisome and that such variability is justified by clinical differences between patients (Arts, Voncken, Medlock, Abu-Hanna, & van Weert, 2016;Cook et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Surgical site infections (SSIs) are the third most frequent cause of nosocomial infections, increasing the rates of morbidity and mortality, and the costs and length of hospitalisation. Administration of surgical antibiotic prophylaxis (SAP) could reduce the risk of SSIs and their related complications . The main goal of SAP is to reduce the burden of microorganisms at the surgical site during an operation .…”
Section: Introductionmentioning
confidence: 99%
“…Administration of surgical antibiotic prophylaxis (SAP) could reduce the risk of SSIs and their related complications. 1,2 The main goal of SAP is to reduce the burden of microorganisms at the surgical site during an operation. 3 To achieve this goal, the most common pathogens associated with the surgical procedures should be considered.…”
Section: Introductionmentioning
confidence: 99%